Pengembangan Sistem Telehealth Dengan Diagnosis Penyakit Otomatis Berbasis Web - Micahel Yulius Munthe; Bayu Priyambadha; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Being healthy is a very important thing for human life. Healthy or not a person can affect to them daily activities. In Indonesia, many people who get minimal health handling. It coused by many factors. Some of these factors, such as for people live at the village, the distance between health center is not always close to their residence and for people who live in the city, sometimes don't have time to queue in hospitals or don't get good service from hospitals. Telehealth system can solve health problem handling in Indonesia. Using a telehealth system can help people get closer to their doctors or save time on illness or health care consultations. The result of the development of this telehealth system is the function of consultation with doctor in the form of real-time chatbox where users don't need to reload the page to get the consultation reply. There is also an automatic disease diagnosis function by using a dempster-shafer method where users can diagnose the disease based on symptoms experienced and some other support functions. Requirement functional testing where using whitebox and blackbox testing give result in a 100% success rate. As well as for Non-functional requirement testing of security, compatibility, and performance that is done by using some tools give result in 100% success rate too. Keywords: health handling, telehealth system, automatic, consultation, automatic disease diagnosis